Evaluating the temporal link between the Karoo LIP and climatic–biologic events of the Toarcian Stage with high-precision U–Pb geochronology - Sell, B.; Ovtcharova, M.; Guex, J.; Bartolini, A.; Jourdan, Fred; Spangenberg, J.E.; Vincente, J.; Schaltegger, U. (Elsevier Science BV, 2014)
The Karoo Large Igneous Province (K-LIP) is considered to have substantially influenced global warming, marine anoxia, and concomitant marine extinction in the Toarcian (Lower Jurassic). The sequence and duration of these events has been uncertain thus precluding direct comparison between sedimentary successions and the K-LIP. Two relatively narrow time intervals of the Early Toarcian, one approximately within the lower portion of the H. falciferum ammonite zone and the other near the Pliensbachian–Toarcian boundary (PL–TO-B), have received much attention because they are associated with carbon isotope excursions (CIEs) and marine extinctions. Potential causal mechanisms have been proposed, such as the release of massive amounts of carbon to the atmosphere via a catastrophic magmatic intrusive episode related to the K-LIP. Here we test the timing with four new high-precision (CA-ID-TIMS) U–Pb zircon ages from the Toarcian stage, collected from tephra interstratified with ammonite-bearing carbonates in southernmost Peru. We also present new U–Pb zircon and baddeleyite data from three sills and one rhyolite of the K-LIP in South Africa. Our new data permit a substantial reinterpretation of the Toarcian timescale: The Pliensbachian–Toarcian boundary (PL–TO-B), a prominent global extinction level, must be older than 183.5 Ma on the basis of our oldest tephra. The H. falciferum CIE (equivalent to the so-called Toarcian oceanic anoxic event) is bracketed by two ash-fall bed dates between 183.22±0.26183.22±0.26 and 181.99±0.13 Ma181.99±0.13 Ma (all 2σ analytical and tracer errors); the CIE duration is estimated at approximately 300 ka on the basis of minimum error interpolation of ammonite zone boundaries. The base of the H. falciferum CIE appears to correlate in time with the onset K-LIP sill emplacement dated by the oldest sill at 183.014±0.072 Ma183.014±0.072 Ma. However, sill emplacement appears to have lasted for a minimum of 2 million years, at least until 181.31±0.19 Ma181.31±0.19 Ma, which is in disagreement with a short duration of the H. falciferum negative CIE. Furthermore, our data suggest that the timing of the main volume of the K-LIP may have been approximately 4–5 Ma. This prolonged and possibly pulsed magmatic activity of the K-LIP may be correlated with extinction pulses and climate changes in the Middle and Late Toarcian Stage, each event occurring within a unique set of global environmental conditions.